Analysis of Hurricane Track Forecast Accuracy During the 2018 Season - Jonathan D. Unger (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2019)
Hurricane track forecasting has become more accurate in recent years due to technological advances in modeling methods. However, due to the complex nature of the relationship between oceanic and atmospheric variables and hurricane tracks, noteworthy errors in track prediction, especially for predictions several days into the future, still remain. In this study, two different methods of forecasting hurricane tracks are compared. Using the four United States landfalling hurricanes of the 2018 season as a sample, the official forecast tracks published by the National Hurricane Center (NHC) and hypothetical tracks based purely on climatology were mapped simultaneously with the preliminary best track published by the NHC. The forecast tracks were generated by the NHC using a synthesis of various types of models, and the climatological tracks were generated using a weighted average of historical cyclone tracks. The results indicate that the official forecasts often performed better than the purely climatological tracks using the preliminary best track as a point of reference. These conclusions support the common understanding that climatological data alone are not sufficient for highly accurate hurricane track prediction, as current oceanic and atmospheric conditions must be incorporated into the models to reach higher levels of accuracy.
Keywords: hurricane; track; forecast; accuracy; 2018